Defeat and deliverance: prefigurements of the Jewish revolt against Rome in Josephus' depictions of past invasions of Jerusalem - Henderson, Jordan (Journal for the study of Judaism / Supplements, 2026)
"This monograph examines Josephus' depictions of foreign invasions of Jerusalem in his Antiquitates Judaicae. These include the invasions of Shishak, Sennacherib, Nebuchadnezzar, Alexander the Great, Antiochus IV Epiphanes, and Pompey the Great. In examining these narratives, the book approaches the Antiquitates Judaicae as an extended "prequel" or backstory to his earlier Bellum Judaicum, examining the ways in which these narratives foreshadow and invite comparisons with his prior account of the war with Rome. The book also explores these narratives within the literary context of the Antiquitates Judaicae as a whole and the ways Josephus' perceived audience expectations may have influenced his depictions of these events"-- Provided by publisher